Influence of Teaching and the Teacher’s Feedback Perceived on the Didactic Performance of Peruvian Postgraduate Students Attending Virtual Classes During the COVID-19 Pandemic - Bazán-Ramírez, Aldo; Capa-Luque, Walter; Bello-Vidal, Catalina; Quispe-Morales, Rolando (Frontiers in Education, 2022)
Educational researchers have become interested in the study of Teaching and Feedback processes as important factors for learning and realizing achievements in the teaching-learning context at the undergraduate and postgraduate levels. The main objective of this research was to assess the effect of five variables of the teacher’s didactic performance (two from Teaching and three from Feedback) on the self-assessed evaluation and application, mediated by their performances in Participation, Pertinent practice and Improvement. Participants were 309 Peruvian masters and doctoral students of an in-person postgraduate course in Educational Sciences who, due to the COVID-19 pandemic, were attending classes and submitting assignments and exercises online. Students were asked to fill two online questionnaires in Google Forms format regarding didactic performance; the first questionnaire comprehended five dimensions of teacher performance: Explicitness of criteria, Illustration, Supervision of learning activities, Feedback, and Evaluation, whereas the second one encompassed four dimensions of student performance: Illustration – Participation, Pertinent practice (Adjustment to supervision of practices), Feedback – Improvement, and 4. Evaluation – Application. When tested, two structural regression models showed (with good goodness-of-fit values) that the Evaluation – Application student performance factor was significantly and similarly predicted by the Illustration – Participation and Feedback – Improvement student performance variables, and, to a lesser extent, yet significantly, by the Pertinent practice student performance. Moreover, teacher performances had a significant effect with high regression coefficients on the three student performance variables included as mediators, both when the five teacher performance variables were included as predictor variables, and when arranged into two second-order factors (Teaching and Feedback).